PENYULUHAN KESEHATAN JANTUNG - PEMBULUH DARAH DI DESA MENJING, PANDEYAN, NGEMPLAK, BOYOLALI - Mei Kusumaningtyas; Herdianty Kusuma Handari (Jurnal Pengabdian Masyarakat Fisioterapi dan Kesehatan Indonesia, 2022)
Hypertension is one of the big challenges in Indonesia due to the lack of attention and knowledge about heart and blood vessel health in the community. The role of village cadres on Heart and Blood Vessel Health in the community is still inadequate so that the solution that can be taken is counseling about Heart and Blood Vessel Health to the community. The purpose of this community service activity is to increase public knowledge about heart and blood vessel health in Menjing Village, Pandeyan, Ngemplak, Boyolali. The method of implementing this community service is by: counseling about heart and blood vessel health, training on heart and blood vessel health screening including measuring blood pressure, implementing blood pressure measurements in the community. The implementation of community service is carried out in Menjing Village, Pandeyan, Ngemplak, Boyolali, Central Java Province in September – October 2021. The output targets of community service activities are: increasing public understanding of heart and blood vessel health, and increasing knowledge and skills of Menjing Village cadres, Pandeyan, Ngemplak, Boyolali to measure blood pressure Keywords: hypertension, heart, blood vessels, blood pressure